2021
DOI: 10.3390/su14010378
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Human Activity and the Urban Heat Island Effect in Melbourne and Four Other International Cities Impacted by COVID-19

Abstract: Climate change is one of the biggest challenges of our times, even before the onset of the Coronavirus (COVID-19) pandemic. One of the main contributors to climate change is greenhouse gas (GHG) emissions, which are mostly caused by human activities such as the burning of fossil fuels. As the lockdown due to the pandemic has minimised human activity in major cities, GHG emissions have been reduced. This, in turn, is expected to lead to a reduction in the urban heat island (UHI) effect in the cities. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…However, this study fulfills the limitations and recommendations of some other studies. For example, Wai et al, (2022) recommended that investigating the ongoing pandemic situation by specifically observing the LST variation from a satellite image analysis between the years 2020 and 2021 would provide a better representation on the effects of human movement restrictions towards the UHI intensity [28]. Lastly, there are numerous different methods for assessing heat island zones and mapping heat island intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study fulfills the limitations and recommendations of some other studies. For example, Wai et al, (2022) recommended that investigating the ongoing pandemic situation by specifically observing the LST variation from a satellite image analysis between the years 2020 and 2021 would provide a better representation on the effects of human movement restrictions towards the UHI intensity [28]. Lastly, there are numerous different methods for assessing heat island zones and mapping heat island intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The principal causes of the UHI [23][24][25][26] include the alteration of surface form, surface structure, fabric, and property changes that are linked with urbanization and the subsequent change in climate. Nevertheless, UHI is also influenced by human activities that emit anthropogenic heat (AHR) [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pre-pandemic conditions, UHI phenomena in major cities in the world have been observed to be increasing annually, particularly in the winter (Manoli et al 2019 ). The Covid-19 pandemic period, when majority of the cities were under strict lockdown and/or extremely reduced human activities, was a unique condition to investigate the influence of anthropogenic activities on LST (and hence UHI phenomenon) (Wai et al 2022 ). A number of studies reported a reduction in LST (and hence UHI effect) during the pandemic period (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported a reduction in LST (and hence UHI effect) during the pandemic period (e.g. El Kenawy et al 2021 ; Jallu et al 2022 ; Liu et al 2022 ; Saputra et al 2022 ; Wai et al 2022 ). The key reason for variations in UHI during the lockdown period was reported as the reduction in greenhouse gas emissions (El Kenawy et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%